Dauciform roots affect the position of the neighboring plants on the economic spectrum in degraded alpine meadows - Fan, Rong; Huang, Yulin; Liu, Wanting; Jiang, Songlin; Ji, Wenli (Frontiers in Plant Science, 2023)
Background and Aims Special root structures that can dissolve insoluble phosphorus locked in soil are supposed to contribute not only to the growing status of themselves but also to the neighbouring plants. However, whether dauciform roots have any effect on the neighbouring plants and how does it respond to meadow degradation had not been studied.Methods Alpine meadows with different degradation statuses were selected and the functional traits of Carex filispica and the co-occurring species Polygonum viviparum were measured to explore their response to degradation, as well as the response of Polygonum viviparum to the dauciform roots of Carex filispica.The results showed that 1) the number of dauciform roots decreased with the intensifying degradation, positively related to available phosphorus in the soil and negatively related to the aboveground phosphorus of Carex filispica. 2) Carex filispica and Polygonum viviparum are similar in specific leaf area and specific root area, yet different in the phosphorus content. The available phosphorus in the soil was negatively related to the aboveground phosphorus of Carex filispica and positively related to that of Polygonum viviparum. 3) When lightly degraded, the proportion of dauciform roots had positive effects on the aboveground resource-acquiring traits of Polygonum viviparum, which were no longer significant at heavy degradation. 4) Polygonum viviparum and Carex filispica without dauciform roots have similar performance: a decrease of belowground carbon with the increasing degradation, and a trend toward resource conservation with the increasing proportion of dauciform roots, which did not exist in Carex filispica with dauciform roots.Conclusions Our study found that dauciform roots had a beneficial effect on the resource acquisition of their neighbouring plants. However, due to the uncontrollable nature of natural habitats, whether this effect is stable and strong enough to be performed in ecological restoration requires further lab-controlled studies.